ANALISIS FAKTOR-FAKTOR KEUANGAN PERUSAHAAN YANG MEMOTIVASI TINDAKAN AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2000-2007 - Putri Oktavia; Syarief Fauzi (Departemen Ekonomi Pembangunan USU, 2013)
The object of this study is to analyze the factors of financial ratios that affect a company in taking the company’s acquisition strategy. The financial ratios, in this study, used are Price Earning Ratio (PER), Debt to Equity Ratio (DE), Return On Investment (ROI), Net Profit Margin (NPM), Earning per share (EPS), Equity per share (EqPS) and Leverage Ratio (LR). In this study the data used are secondary data, while the population used the companies listed on the Indonesia Stock Exchange and do acquisition activity in the period 2000-2007. Sampling method in this research is by using purposive sampling, which in this study using the 30 firms which 15 companies conducting acquisitions and 15 companies that do not conduct acquisitions. The method of analysis used in this study is the logistic regression analysis (Logistic Regression).Keywords : Acquisition, Financial Ratios